2010
DOI: 10.1073/pnas.1003374107
|View full text |Cite
|
Sign up to set email alerts
|

Divalent counterion-induced condensation of triple-strand DNA

Abstract: Understanding and manipulation of the forces assembling DNA/ RNA helices have broad implications for biology, medicine, and physics. One subject of significance is the attractive force between dsDNA mediated by polycations of valence ≥3. Despite extensive studies, the physical origin of the "like-charge attraction" remains unsettled among competing theories. Here we show that triplestrand DNA (tsDNA), a more highly charged helix than dsDNA, is precipitated by alkaline-earth divalent cations that are unable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 41 publications
10
75
0
Order By: Relevance
“…ES forces between these periodic arrays of charges might turn from repulsion to attraction for well-neutralized DNA duplexes. Attractive DNA-DNA forces have been systematically measured in solutions of some di-and many tri-valent cations at E1 nm between DNA surfaces, [46][47][48]55 Fig. 2, while purely repulsive ES forces are detected in solutions of monovalent salts.…”
Section: Dna-dna Es Forces: Repulsion Vs Attractionmentioning
confidence: 99%
“…ES forces between these periodic arrays of charges might turn from repulsion to attraction for well-neutralized DNA duplexes. Attractive DNA-DNA forces have been systematically measured in solutions of some di-and many tri-valent cations at E1 nm between DNA surfaces, [46][47][48]55 Fig. 2, while purely repulsive ES forces are detected in solutions of monovalent salts.…”
Section: Dna-dna Es Forces: Repulsion Vs Attractionmentioning
confidence: 99%
“…(2) For a system of loop-tethered short helices, the SAXS experiments suggested a possible weak side-side helix-helix attraction in a Mg 2+ solution of high concentration (*0.6 M) [68]. (3) The experiments showed that the PB theory underestimates the efficiency of Mg 2+ in RNA structural collapse by over 10 times [184]. (4) In trivalent ion solution, short DNA duplexes can become condensed while RNA duplexes keep soluble [185].…”
Section: Ion-mediated Structural Collapsementioning
confidence: 98%
“…(4) In trivalent ion solution, short DNA duplexes can become condensed while RNA duplexes keep soluble [185]. (5) Mg 2+ cannot condense long DNA duplexes while could condense short DNA triplex in aqueous solution [181,184].…”
Section: Ion-mediated Structural Collapsementioning
confidence: 99%
“…A SC analysis seems potentially compatible and could provide some rational basis to the effective parameters of the KL theory [51,8,55,48,56].…”
Section: Validity Domain and The Point-like Limitmentioning
confidence: 99%